Eyewitness identification procedures: Do researchers and practitioners share the same goals?. (March 2021) - Pike, Graham; Havard, Catriona; Harrison, Gini; Ness, Hayley
Research has undoubtedly led to a number of important changes to the way police obtain eyewitness identification evidence in a number of countries. However, despite these successes and the significant effort made by researchers to communicate key findings to public agencies, policy-makers and influential law enforcement personnel using a broad range of evidence, relevant policy and practice have either been very slow to respond or have not changed to incorporate the suggestions at all. In this article we employed an online survey to explore the knowledge and opinions of front-line policing practitioners in the UK regarding eyewitness research and practice. This was undertaken to determine how familiar less-senior, operational staff were with key research findings, what their opinions of current practice were and crucially, their views on how identification procedures should be improved compared with the recommendations made by researchers. The results revealed a fundamental mismatch between research and practice, with practitioners indicating a need to increase the rate of positive identifications and research tending to focus on methods of reducing false identifications. This result suggests that an approach driven by the need for the police to produce convictions may be an important factor that is blocking the translation of eyewitness identification research into practice.